Chipped Pharmaceuticals from Production to in VIVO (in body) Drug Delivery Becoming Reality - Jones, Erick; Gupta, Shalini; Jefferson, Felicia; Rogers, Jamie; Choi, Jae Bong; Bolton, Joshua; Cochran, David (ExcelingTech, 2015)
Abstract—Researchers previously researched on theories on advances in medical technologies. Building upon advances in medical technology that collect measured data to facilitate patient diagnosis and business decisions. This research extends production can further meet ongoing need for the healthcare industry that focuses upon pharmaceuticals processes to improve item tracking and data collection. These improvements may lead to improving quality of care while reducing cost. Similar to previous research we focus on the remote, non-invasive characteristics of RFID that can provide information without imposing additional burden onto the patient or staff. We suggest that RFID enabled devices can provide convenient and accurate data for disease diagnosis, evaluation of prescription non-compliance and identification of medication dosage errors. This paper builds upon previous research to describe the background of RFID tracking system that begins with compliance documentation from the drug manufacturer through confirmation of patient compliance by capsule extraction from the bottle, into a pill case and ultimately ingested or inserted into the body. This transcript provides additional information about healthcare trends in order to motivate the need for a biocompatible RFID system. We distinguish this research from our earlier research with a table that shows how production and warehousing can be integrated on the backend to reduce costs.Keywords— RFID; e-pedigree; pharmaceuticals; tracking